Exploring the Impact of Cashless Payment Systems on Impulsive Buying Behavior among Generation Z Consumers - Yu, Michelle P. (International Review of Management and Marketing, 2026)
The study explores cashless payment factors influencing Gen Z’s impulsive buying, analyzing demographics, preferences, and key influencing factors. Correlations and differences by demographics are tested and possible interventions are derived. A descriptive survey design was employed to administer a researcher-made questionnaire to 259 Gen Z respondents from Cantilan, Philippines. Descriptive and inferential statistics (Pearson correlation, Mann-Whitney U, MANOVA) were used to determine the relationship of gender and means of payment to impulsive buying tendencies. The analysis revealed that cashless payment systems facilitate impulse buying for Gen Z driven by promos, trust and security, and social media influence purchases, especially in fashion and food and beverage with males being the most influenced. There were significant gender differences, finding that males were more influenced by cashless payment convenience and Promotions than females, while social media influenced both genders equally. Theoretical implications involve contributions of a new model factoring in drivers missing in other studies. Managerial implications alert for responsible cashless payment system developments, and fintech developers can help counter impulsive buying behaviors with system solutions like “impulse delay.” Educators and lawmakers can target social media and promo influence in financial literacy training.